A method of measuring cochlear potentials evoked by two-tone excitation - Michalski, Wojciech; Dziewiszek, W.; Bochnia, M. (Archives of Acoustics, 2006)
This paper presents a new method of measuring cochlear microphonics (CM) evoked bya two-tone acoustic wave. The method is based on phase sensitive detection whereby it ispossible to precisely measure not only excitation frequency CM signals but also combinationsignals. The method can be used in experiments conducted on animals. Exemplary experimentalresults are given.